2010
DOI: 10.1186/1751-0147-52-61
|View full text |Cite
|
Sign up to set email alerts
|

Associations among systemic blood pressure, microalbuminuria and albuminuria in dogs affected with pituitary- and adrenal-dependent hyperadrenocorticism

Abstract: BackgroundHypertension and proteinuria are medical complications associated with the multisystemic effects of long-term hypercortisolism in dogs with hyperadrenocorticism (HAC).MethodsThis study investigated the relationships among adrenocorticotropic hormone (ACTH)-stimulation test results, systemic blood pressure, and microalbuminuria in clinically-healthy dogs (n = 100), in dogs affected with naturally occurring pituitary-dependent (PDH; n = 40), or adrenal-dependent hyperadrenocorticism (ADH; n = 30).Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 27 publications
4
41
1
9
Order By: Relevance
“…31 Systemic hypertension has also been found to frequently be associated with other systemic disease in dogs, including hyperadrenocorticism and diabetes mellitus. 32,33 Five of the six dogs with systemic hypertension in this study had the disease in conjunction with hyperadrenocorticism or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 88%
“…31 Systemic hypertension has also been found to frequently be associated with other systemic disease in dogs, including hyperadrenocorticism and diabetes mellitus. 32,33 Five of the six dogs with systemic hypertension in this study had the disease in conjunction with hyperadrenocorticism or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, Tvarijonaviciute et al (2013) reported a significant decrease of the urinary albumin/creatinine ratio in healthy dogs after weight loss. Microalbuminuria was not observed in dogs with hyperadrenocorticism (Lien et al 2010), cisplatin-induced azotemia (Autio et al 2007) or in Labradors and Golden Retrievers exposed to Borrelia burgdorferi .…”
Section: Albuminmentioning
confidence: 84%
“…Diagnosis of hyperadrenocorticism had been based on clinical signs (such as polydipsia, polyuria, polyphagia, decreased activity level, panting, a pot-bellied appearance, excessive hair loss or alopecia in general, chronic pyoderma) and the results of routine serum biochemical analyses (such as elevation of hepatic enzyme activities), affirmative adrenocorticotropic hormone stimulation test results and adrenal ultrasonographic images [12]. Stabilized hyperadrenocorticism was defined as alleviation of clinical signs (polydipsia and/or polyuria, activity level and panting) and reduced excretion of post-ACTH cortisol within the therapeutic range (< 10 μg/dL) after four weeks of trilostane treatment.…”
Section: Methodsmentioning
confidence: 99%